Peran Aliran Progresivisme dalam Pengembangan Karakter Siswa Muslim - atmaja, ibrahim (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2024)
Education plays a crucial role in shaping a quality generation, where the development of Muslim students' character is one of the key aspects that must be addressed. In the context of Islamic education, character relates not only to academic aspects but also to morals, ethical values, and social skills. The progressive movement offers an innovative approach to education, emphasizing active learning and relevance to everyday life. John Dewey, a key figure in progressivism, argued that education should be relevant and help students develop critical thinking and problem-solving skills. This study employs a literature review, gathering relevant sources. By applying the principles of progressivism, Muslim students can explore their identities and implement Islamic values in real actions. Moreover, this approach supports collaboration and social interaction, which aligns with the value of ukhuwah in Islam. Progressivism also encourages the development of critical thinking, creativity, and innovation, essential for facing challenges in the global era. Through progressive education, students not only acquire knowledge but also develop a strong character in line with Islamic values. The integration of progressive principles with religious values is highly relevant for shaping a generation that is intellectually capable, moral, and ethically sound. This study examines the concrete implementation of the progressive movement in character education for Muslim students, as well as the challenges and opportunities encountered in the procss.